Pedagogical Culture of Teachers at Technical Universities for Safe Educational Process During the War in Ukraine. - Natalia Tverdokhliebova; Nataliіa Yevtushenko (Educational Challenges)
The entire education system is currently undergoing structural changes, which are reflected in the increased use of digital and distance learning technologies. Pedagogical culture as a personal characteristic of a teacher acts as a means of implementing professional activities in the unity of goals, objectives, as well as means and results. Simultaneously, different types of pedagogical activity form the functional structure of culture. The main features of pedagogical activity should be its complexity and integrity, creative nature, a combination of collective activity and individual creativity of teachers, because the process of solving pedagogical goals and objectives is a technology of pedagogical activity that characterizes the mode of existence and functioning of the teacher’s pedagogical culture.